Brentuximab vedotin for the treatment of patients with relapsed or refractory Hodgkin lymphoma after autologous stem cell transplantation. (6th October 2019) - Kaloyannidis, Panayotis; Hertzberg, Mark; Webb, Kate; Zomas, Athanasios; Schrover, Rudolf; Hurst, Michael; Jacob, Ian; Nikoglou, Thalia; Connors, Joseph M.
Summary: Brentuximab vedotin (BV) is the first approved novel agent for salvage treatment of relapsed or refractory (R/R) classical Hodgkin lymphoma (cHL) after autologous stem cell transplantation (ASCT). In this study, a literature‐based analysis was undertaken to assess, via an indirect treatment comparison, the comparative efficacy of BV to salvage chemotherapy as treatment for R/R cHL patients following ASCT. This comparative effectiveness research was undertaken to support a reimbursement submission for BV to the Australian Pharmaceutical Benefits Advisory Committee. Retrospective analysis of individual patient data from four data sources demonstrated that the use of BV as first salvage treatment in cHL patients relapsing or progressing post‐ASCT achieved improvements in both clinical response and overall survival. More specifically, BV was associated with an incremental improvement of 22% in overall response rate compared to salvage chemotherapy. Five‐year overall survival and progression‐free survival rates were 92·2% [95% confidence interval (CI): 85·5–99·3%] and 32·2% (95% CI: 19·1–54·6%) respectively for BV, compared to 30·5% (95% CI: 22·2–42·0%) and 3·2% (95% CI: 1·1–8·9%) respectively for salvage chemotherapy. The encouraging results from this conservative analysis have the potential to support informed clinical management and funding decisions for the first salvage of cHL patients demonstrating recurrence after ASCT.